2019
DOI: 10.1038/s41598-019-44550-3
|View full text |Cite
|
Sign up to set email alerts
|

Poor control of interference from negative content hampers the effectiveness of humour as a source of positive emotional experiences

Abstract: The brain-based ability to direct attention away from interfering negative information may co-determine to which degree one may benefit from humour as a source of positive emotional experiences. This should be particularly relevant when it comes to humour that implicates a target the joke makes fun of, which inherently entails rivalry between positive and negative emotional representations. One hundred healthy individuals completed a pictorial negative affective priming task and a nonverbal humour processing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Even though, facial activity in association with amusement has shown greater coherence with the experience of emotion than all other basic emotions (Durán et al, 2017). Therefore, the current findings indicate marked interindividual variability in the expression of humor, which could be related to many variables that remain to be elucidated (such as emotional regulation abilities, social anxiety, Theory of Mind skills, motivation, gelotophobia and personality traits, among others; Canal et al, 2019; Ezrina & Valian, 2023; Papousek et al, 2019; Ruch et al, 2015). This suggests that the humor process is highly complex, and points to the importance of developing methods to elicit mirth and determine the point at which it has been elicited.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Even though, facial activity in association with amusement has shown greater coherence with the experience of emotion than all other basic emotions (Durán et al, 2017). Therefore, the current findings indicate marked interindividual variability in the expression of humor, which could be related to many variables that remain to be elucidated (such as emotional regulation abilities, social anxiety, Theory of Mind skills, motivation, gelotophobia and personality traits, among others; Canal et al, 2019; Ezrina & Valian, 2023; Papousek et al, 2019; Ruch et al, 2015). This suggests that the humor process is highly complex, and points to the importance of developing methods to elicit mirth and determine the point at which it has been elicited.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, our results using pictures parallel those of Fiacconi and Owen (2015), who used verbal jokes; as in their study, the accelerative component of the HR response can be better interpreted as reflecting the positive emotion associated with humor appreciation, even when the Erotic pictures did not prompt cardiac acceleration. The results of a more recent study (Papousek et al, 2019), and the consistently reported relationship between humor ratings and the degree of HR acceleration (Fiacconi & Owen, 2015; Lackner et al, 2013), support this interpretation. Moreover, erotic pictures have been reported previously to elicit “the least peak acceleration” relative to other pleasant pictures (Bradley et al, 2001).…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, it can be thought that individuals increase their psychological resilience by using humor. It can be thought that this effect of humor, which is one of the sources of positive emotional experiences, on psychological resilience arises from the positive relationship between psychological resilience and having positive emotional experiences (Papousek et al, 2019;Judd, 2016).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Another factor that is effective in increasing psychological resilience is having positive emotional experiences (Judd, 2016). One of the sources of positive emotional experiences is sense of humor concept associated with positive psychological structures (Papousek et al, 2019;Maiolino and Kuiper, 2014). Psychological functions of humor include the cognitive and social benefits of the positive emotion of mirth, and its uses as a form of social communication and influence, and as a way of relieving tension, regulating emotions and coping with stress (Martin, 2006).…”
mentioning
confidence: 99%